1999
DOI: 10.1183/09031936.99.13361699
|View full text |Cite
|
Sign up to set email alerts
|

Proximal pulmonary emboli modify right ventricular ejection pattern

Abstract: Proximal pulmonary emboli modify right ventricular ejection pattern. A. Torbicki, M. Kurzyna, M. Ciurzynski, P. Pruszczyk, R. Pacho, A. Kuch-Wocial, M. Szulc. #ERS Journals Ltd 1999. ABSTRACT: Analysis of the systolic flow velocity curve (SFVC) in the right ventricular outflow tract is considered as an alternative to the tricuspid valve pressure gradient (TVPG) method for echo-Doppler assessment of pulmonary arterial pressure (Ppa). The present study checked whether or not SFVC is affected by the cause of pulm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
48
0
6

Year Published

2008
2008
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 97 publications
(55 citation statements)
references
References 17 publications
1
48
0
6
Order By: Relevance
“…Characteristic changes of the flow profile in the PA due to pressure reflection with a notch after peak velocity (see Figure 2) have been described in patients with pulmonary embolism. 8,9 In the presence of a notch, we should suspect increased PVR, but absence of the notch has a low predictive value. In patients with PAH, we have shown in a recent study that PVR can be calculated with a strong correlation (Rϭ0.93) between catheter and Doppler methods.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Characteristic changes of the flow profile in the PA due to pressure reflection with a notch after peak velocity (see Figure 2) have been described in patients with pulmonary embolism. 8,9 In the presence of a notch, we should suspect increased PVR, but absence of the notch has a low predictive value. In patients with PAH, we have shown in a recent study that PVR can be calculated with a strong correlation (Rϭ0.93) between catheter and Doppler methods.…”
Section: Discussionmentioning
confidence: 99%
“…This phenomenon has been studied invasively and by Doppler echocardiography in patients with pulmonary embolism. 8,9 However, to the best of our knowledge, there are no studies that have used Doppler echocardiography for a comprehensive description of pressure reflection, the effects of pressure reflection on PA flow, and the right ventricle pressure profile. In the present study, we hypothesize that pressure reflection and its effect on the right ventricle pressure profile can be described noninvasively by Doppler echocardiography.…”
Section: Clinical Perspective On P 432mentioning
confidence: 99%
“…2,3,[7][8][9][10][11] However, the overall applicability and accuracy of the above-described methods are controversial. [12][13][14][15][16] Additionally, various authors 10,11,17,18 have observed spatially highly inhomogeneous cross-sectional flow profiles and fractions of retrograde flow during systole and diastole in the main pulmonary artery in patients with PH. This was not observed in normal subjects.…”
Section: Clinical Perspective See P 30mentioning
confidence: 99%
“…In addition, AcT tended to be shorter with more distal Doppler sample volume positions [13,14] in individuals with body surface area .2.0 m 2 and in adults .30 yrs old [15]. Due to these limitations, the measurement of time intervals with pulsed wave Doppler as a method of estimation of Ppa was practically eliminated from clinical practice, while their potential role in assessment of components of pulsatile haemodynamics still remain largely unexplored [16,17].…”
Section: Diagnostic Value Of Echocardiography and Its Role In Screenimentioning
confidence: 99%